The 5S Methodology in Regular Basic Education Institutions in Peru - Noriega-Araníbar, María Teresa (2025)
This study aims to describe how the implementation of the 5S methodology contributes to the development of a quality culture in regular basic education institutions in Peru. A qualitative, non-experimental, and descriptive research design was employed, using semi-structured interviews conducted with informed consent. The sample consisted of four educational institutions, selected to explore perceptions regarding the benefits of implementation. The findings revealed a lack of formal planning in the implementation process, which was typically initiated by a teacher or principal and carried out with trained student leaders. Reported benefits include improvements in the classroom environment, communication spaces, waste reduction, and student performance—factors that collectively foster a culture of quality.